"Price Tag" of Risk of Using E-Payment Service. Issue 3 (2nd July 2020) - Ho, Kevin K. W.; See-To, Eric W. K.; Chiu, Dickson K. W.
Abstract: In this research, the authors utilized a survey to evaluate the notional values of the overall risk, the privacy risk, and the financial risk of using a credit card and an RFID-based E-payment service from risk-neutral and risk-averse users. With the known extra financial risk (in terms of monetary value) to be faced by the users in using two different versions of an RFID-based E-payment service, the authors determined the notional monetary value of the extra privacy risk posed by providing personal and financial information to the E-payment service and the differences in the risk aversion of the two groups of users. The findings may help E-payment service developers design better E-payment services based on a better understanding of the value of personal data in their users' perspectives and, thus, help determine the appropriate incentives for attracting users to use their services.